Teaching boys : developing classroom practices that work - Keddie, Amanda (Allen & Unwin, 2007)
Persistently cheeky, disruptive, even aggressive boys can be found in classrooms everywhere, as can the victims of bullying. These boys' behaviours often pose a problem to themselves as well as to others. As the hotly contested debates about boys' education swirl around them, what can teachers actually do to improve boys' performance in the classroom?\Teaching Boys provides a practical framework for teachers to improve boys' education in ways that are appropriate for their school context and also sustainable. Drawing on intensive research in classrooms where innovative teachers are achieving good outcomes with boys, Keddie and Mills show how other teachers can learn from their success. They acknowledge that there are no simple solutions, but show that what teachers do in the classroom really does matter. They emphasise the importance of understanding the impact of dominant and subversive masculinities at all levels of schooling, on both boys and girls.